Lessons learned developing and deploying a provincial virtual mental health support during the COVID-19 pandemic. Issue 4 (July 2022) - Strudwick, Gillian; Risling, Tracie; Kassam, Iman; Shin, Hwayeon Danielle; Moss, Tyler; Carlberg, Courtney; Zhou, Wenjia
Significant efforts have been put into implementing virtual forms of healthcare and supports since the beginning of the pandemic. However, limited information has been shared with health leaders about how this has taken place, and what can be learned from this to move forward into the future. The purpose of this article is to describe lessons learned co-designing and developing a virtual health support during the COVID-19 pandemic in the province of Saskatchewan. In this article, we anchor these lessons learned on a specific virtual health service support, "SaskWell, " which offers a digital service, and aims to connect residents of the province to digital mental health supports and resources.